PERSEPSI SISWA TENTANG PELAKSANAAN PRAKTIK LAPANGAN (PL) MAHASISWA STKIP PGRI SUMATERA BARAT SEMESTER GANJIL 2013/2014 DI MAS. TI BATANG KABUNG PADANG - -, Nurjanah - (Pendidikan Sosiologi, 2014)
Supposedly between students and teachers (OT student) well-established interaction in order to create a fun learning atmosphere, but realitiasnya between students and students interact with the PL looks less good. The purpose of this study is to analyze in depth the students perceptions about the implementation of OT students STKIP PGRI SUMBAR semester 2013/2014 in MAS. TI Batang Kabung. This research is qualitative. Choose informant purposive sampling totaling 19 students of class X and class that specialy class XI student studying with PL. Data collection by observation, interview, willing documentation and triangulation of data. Analysis of the data using interactive by Milles and Huberman. Results illustrate that in delivering learning material is difficult to understand but most students expressed a clear and easily understood material, teaching methods of lecture and question and answer. Management class class less able to control discipline, but in Biology and English learning, classroom discipline is maintained. Nice and interesting learning media but rarely use the media to learn. In Sociology of learning, students respond well but less pleasant learning atmosphere. Learning Biology, less learning interactions go well. Learning English learning atmosphere cool, but in learning Mathematics studies less cool atmosphere. Assessment study has been carried out properly. The use of language is less clear and less well when explaining the lesson.